Protective Effect of Pycnogenol on Kidney Tissue in Rats Undergoing Ionizing Radiation - Arzu Gezer (Anadolu Hemşirelik ve Sağlık Bilimleri Dergisi, 2021)
Aim: Serious complications of radiation use in cancer treatment include kidney toxicity. Pycnogenol®, consisting of phenolic compounds, can be used as a complement to the treatment of some cancers due to its good tolerability, high anti-oxidant effect and safety. The aim of this study was to histopathologically evaluate the protective effects of Pycnogenol on rat kidney tissue of high doses of ionized radiation (IR). Method: The 32 Sprague-dawley male rats used in the study were randomly divided into 4 groups. Groups; control group, no application was made to rats in this group. The Pycnogenol group was administered to rats in this group with 300 mg/kg of Pycnogenol gavage, which was dissolved with 5% dimethylsulfoxide during the experiment and at the same time of day. In the IR group, rats in this group were subjected to a total of 30 Gy of radiation in 3 days, 10 Gy in a single fraction at the same time in the first, second and third days of the study. Radiation applications were performed in the form of a single dose of total body radiation using gamma rays. The IR + Pycnogenol group gave rats in this group 10 Gy in a single fraction on the first, second and third days of the study and 30 Gy in a total of 3 days of radiation. 300 mg/kg of Pycnogenol was continued with gavage until the end of the experiment, and at the end of the two-week experiment period, the renal tissues of rats belonging to all groups were histopathologically evaluated by Hematoxylene-Eosin staining. Results: Degenerative and necrotic changes in interstitial tissue and renal tubule and interstitial nephritis are observed in the radiation groups, while changes and damage were statistically less in the IR+Pycnogenol group. Conclusion: When the study findings were evaluated, it was determined that IR-related damage to kidney tissue could be mitigated by Pycnogenol administration.